An exploration of the prior conceptual understanding of measurement of first year national certificate (vocational) Engineering students - Vale, Pamela (Rhodes University, Faculty of Education, Department of Education, 2017)
Measurement is acknowledged to be a critical component in mathematics education and is particularly important for vocational Engineering students, for whom this is a key skill required in the workplace. The goal of this research was to explore the existing measurement conceptualisations of vocational Engineering students at the outset of their course, as evident in their engagement with mediated measurement tasks. The focus on students' prior knowledge in measurement, was for the value that this awareness holds in understanding the learning needs of the students. Students participated in five measurement tasks. Four took the form of dynamically assessed task-based interviews, and the fifth was a written test assessing what they had learned during their Mathematics classes. Domains of measurement that were assessed in these tasks included length, area, surface area, volume and flow rate. The interviewer took the role of mediator and students were assessed according to the number of moments of mediation and the degree of mediation required to successfully complete the task. Students' responsiveness to this mediation provided insight as to their conceptualisations of the measurements relevant to the task. This research was exploratory in nature and adopted an open and flexible approach to the data analysis. Critical incidents were identified and coded according to the mediation offered and the actions of the students during the measuring activity. This allowed patterns to emerge that revealed stable and emerging conceptualisations that related to embodied and symbolic aspects of measurement. Evidence was found that for many of these students the link between the embodied and symbolic aspects of the concept was broken. This insight allowed suggestions to be formulated about how better to facilitate these students' learning of measurement.
Keywords: Uncatalogued